MEKTEPKE SHEKEMGI JASTAǴÍ BALALARDÍ MIYNETKE TÁRBIYALAWDA QARAQALPAQ XALÍQ ERTEKLERINIŃ ORNÍ HÁM ROLI - Bekimbetova, A.A.; Alewova, R.Sh. (SCIENCE and SOCIETY, 2025)
The article is devoted to the education of diligence of preschool children through Karakalpak folk tales. The article describes the development of work skills through teamwork, knowledge of the content of work, a reasonable attitude to work, as well as the formation of socially useful skills and abilities.
Keywords: labor education; adult labor; labor skills; formation of moral qualities; folk tales; fiction; development; personality